Mahkamah Syari’ah di Nanggroe Aceh Darussalam: Dalam Lintas Sejarah dan Eksistensinya - Qurrotul Aini (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2016)
Decentralization has opened the space for the establishment of local regulation that triggered public debate whether the localregulations can be justified within the framework of the Unitary State of Republic Indonesia or not. Among the local regulations, there is a phenomenon of 'Sharia Politics' especially in Nanggroe Aceh that its socio-history and socio-cultural of Aceh has a distinctive Islamic tradition. This research is based library research and relies on libraryresearch.The data taken is the literature data by content analysis method. It discusses: first, how should we observe the autonomy and the implementation of Islamic justice in Aceh? Second, why does the issue of Sharia Islam play an important role in the political struggles in Aceh? Third, howgood is the practice of Islam Sharia there? The result of this research can be concluded; first, to determine theautonomy and the implementation of Islamic justice in Aceh, it should beexamined the roots of history since the pre-colonial era to the independence and socio-cultural era. Second, the process of transitionfrom the Religious Court to the ShariaCourt establish some regulation or Qanun related to institutions and procedures and categories of Sharia law that within the framework of the Indonesian legal system. Third, during the problematic era of Islam Sharia’s practice, if it did not take seriously and critically thinking, the prospect of Islamic law practice in Aceh would be bad. Because not all Islamic Law can be copied and translated into legislation and article as those applicable in the system of modern governance.